Using Lesson Study to Enhance the Quality of Teaching and Learning in Health Professions Education - John Sandars; David Allan (Acta Medica Iranica, 2024)
Lesson study (LS) offers a systematic, but flexible, approach for enhancing the quality of teaching and learning in Health Professions Education (HPE). There is increasing global use of LS in primary, secondary and higher education, with studies highlighting its impact on enhancing the quality of both teaching and learning through the professional development of teachers. During LS, teachers collaboratively research their own practice with a variety of stakeholders, including students, subject specialists and education experts. The article describes how LS can be practically adapted and implemented in a variety of both academic and clinical settings across the continuum of HPE.